The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.18632/oncotarget.1579
|View full text |Cite
|
Sign up to set email alerts
|

FOXD3 is a novel tumor suppressor that affects growth, invasion, metastasis and angiogenesis of neuroblastoma

Abstract: The transcription factor forkhead box D3 (FOXD3) plays a crucial role in the development of neural crest cells. However, the function and underlying mechanisms of FOXD3 in the progression of neuroblastoma (NB), an embryonal tumor that is derived from the neural crest, still remain largely unknown. Here, we report that FOXD3 is an important oncosuppressor of NB tumorigenicity and aggressiveness. We found that FOXD3 was down-regulated in NB tissues and cell lines. Patients with high FOXD3 expression have greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 47 publications
(71 reference statements)
1
100
0
Order By: Relevance
“…Mutation of miR-584-5p binding site was established with GeneTailor™ Site-Directed Mutagenesis System (Invitrogen) and PCR primers (Supplementary Table S2). Dual-luciferase assay was performed as previously described [11,21,[27][28][29][30]. For promoter and 3′-UTR activity, the luciferase signal was normalized by firefly/Renilla and Renilla/firefly ratio, respectively.…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%
See 3 more Smart Citations
“…Mutation of miR-584-5p binding site was established with GeneTailor™ Site-Directed Mutagenesis System (Invitrogen) and PCR primers (Supplementary Table S2). Dual-luciferase assay was performed as previously described [11,21,[27][28][29][30]. For promoter and 3′-UTR activity, the luciferase signal was normalized by firefly/Renilla and Renilla/firefly ratio, respectively.…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP) assay was performed according to the instructions of EZ-ChIP kit (Upstate Biotechnology, Temecula, CA) [27][28][29][30][31] with antibodies for AGO1, AGO2, zeste homolog 2 (EZH2), histone H3 lysine 27 trimethylation (H3K27me3), and histone H3 lysine 9 dimethylation (H3K9me2; Upstate Biotechnology). Lysates were treated with either RNase H (10 U) or RNase A (20 μg) prior to immunoprecipitation.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%
See 2 more Smart Citations
“…One study demonstrated that FOXD3 regulated RND3 expression and migration properties in melanoma cells (11). Another reported that FOXD3 exhibited tumor suppressive activity that affected the growth, aggressiveness and angiogenesis of neuroblastoma through the transcriptional regulation of NDRG1 (12). However, the role of FOXD3 in lung cancer remains uncharacterized.…”
Section: Introductionmentioning
confidence: 99%